Comparative analysis of VPN network performance using mobile Wi-Fi - Mohd Azli, Fariha; Buja, Alya Geogiana; Saad, Shahadan (College of Computing, Informatics, and Mathematics, 2025)
Virtual Private Networks (VPNs) are widely used to enhance online security and privacy, especially when accessing the internet over mobile Wi-Fi networks. However, performance issues emerge from VPN usage because mobile users experience decreased speed alongside greater latency and packet loss which affect activities such as online gaming, streaming and general browsing. This study explores VPN network performance through mobile Wi-Fi connections by evaluating the services from NordVPN, ExpressVPN, and Surfshark. This study has two main objectives which are to conduct a series of experiments to evaluate how VPNs perform under various usage scenarios, including gaming, streaming, and general browsing, and to analyze the performance of network parameters such as speed, latency, and packet loss across different VPN services. Network performance metrics were measured accurately through experiments conducted with Speedtest by Ookla, PingPlotter and Fing as network monitoring tools. The VPN assessment tests executed across three different environments which simulated actual VPN user operations. Data collection showed strong evidence of performance variations between VPN providers because each provider demonstrated unique deficiencies during the different tests. The research findings help VPN users choose VPNs that match their particular needs while generating valuable optimization opportunities for VPN service providers.